Evaluation of a primary course of H9N2 vaccine with or without AS03 adjuvant in adults: A phase I/II randomized trial. Issue 35 (16th August 2017) - Madan, Anuradha; Collins, Harry; Sheldon, Eric; Frenette, Louise; Chu, Laurence; Friel, Damien; Drame, Mamadou; Vaughn, David W.; Innis, Bruce L.; Schuind, Anne
Highlights: AS03-adjuvanted H9N2 vaccine demonstrated robust immunogenicity in adults. A single-dose vaccination strategy may be feasible for adjuvanted H9N2 vaccines. The adjuvanted formulations permit an 8-fold antigen dose reduction (1.9 vs 15 µg). An anamnestic immune response was observed after a third dose 182 days post-dose 1. All formulations had a clinically acceptable safety profile. Abstract: Background: Avian influenza A H9N2 strains have pandemic potential. Methods: In this randomized, observer-blind study (ClinicalTrials.gov: NCT01659086), 420 healthy adults, 18–64 years of age, received 1 of 10 H9N2 inactivated split-virus vaccination regimens (30 participants per group), or saline placebo (120 participants). H9N2 groups received 2 doses (days 0, 21) of 15 µg hemagglutinin (HA) without adjuvant, or 1.9 µg HA + AS03A, 1.9 µg HA + AS03B, 3.75 µg HA + AS03A, or 3.75 µg HA + AS03B ; followed by the same H9N2 formulation or placebo (day 182). AS03 is an adjuvant system containing α-tocopherol (AS03A : 11.86 mg; AS03B : 5.93 mg) and squalene in an oil-in-water emulsion. Immunogenicity (hemagglutination inhibition [HI] and microneutralization assays) and safety were assessed up to day 546. Results: All adjuvanted formulations exceeded regulatory immunogenicity criteria at days 21 and 42 (HI assay), with seroprotection and seroconversion rates of ≥94.9% and ≥89.8% at day 21, and 100% and ≥98.1% at day 42. Immunogenicity criteria were also met for unadjuvanted vaccine, with lower geometric mean titers. In groups administered a third vaccine dose (day 182), an anamnestic immune response was elicited with robust increases in HI and microneutralization titers. Injection site pain was reported more frequently with adjuvanted vaccines. No vaccine-related serious adverse events were observed. Conclusions: All H9N2 vaccine formulations were immunogenic with a clinically acceptable safety profile; adjuvanted formulations were 4–8 times dose-sparing (3.75–1.9 vs 15 µg HA). Trial registration: Registered on ClinicalTrials.gov: NCT01659086.